Probabilistic Evaluation of Seismic Performance of Steel Buildings with Torsional Irregularities in Plan and Soft Story under Mainshock-Aftershock Sequence - Hamed Kouhestanian; Mohammad Hossein Razmkhah; Jalil Shafaei; Hossein Pahlavan; Mohammad Shamekhi Amiri (Shock and Vibration)
Due to the tectonic plate movement, numerous aftershocks may occur following an earthquake. There are several real mainshock-aftershock ground motion records in which the peak ground acceleration of aftershock is greater than that of the mainshock. Furthermore, irregularities such as soft story and torsional irregularity may change the structural behavior under the influence of earthquakes. This study investigates the fragility curves associated with the three-, five-, and eight-story models with steel moment-resisting frames under the main earthquake and mainshock-aftershock sequence to probabilistically evaluate the aftershock impacts on the steel structures with irregularities in the plan and height. The seismic fragility curves were calculated for four damage levels by selecting the relative displacement capacity at seismic performance levels of slight, moderate, extensive, and complete damage from the US HAZUS code. The analysis was done using structural reliability relationships and incremental dynamic analysis with the OpenSees software platform. The analytical results showed that the structures with soft-story and torsional irregularity were more vulnerable with an increasing number of stories. Also, aftershocks were found to have a more destructive effect on low-rise models. The probability of structural collapse in a given peak ground acceleration for a damaged state due to the mainshock-aftershock sequence is higher than that of the mainshock sequence.